Deconstructing Theology or Prophetic Theology? A Comparative Protestant and Eastern Orthodox Christian Perspective - Nathanael Neacșu (Religions)
The purpose of this paper is twofold: first, to depict, in its main elements, the conception of a Protestant “deconstructive theology”, and, secondly, to present the prophetic aspect of Eastern Christian Orthodox theology in comparison with it. According to the method of “deconstructive theology” as a method, the Scripture must be dismantled in order to be fresh and new. In the Orthodox understanding, the work of theology is understood to be, in the first place, a personal relationship with and experience of God, both from a mystical and sacramental perspective, and, through this, an actualisation of the work and message of God’s Revelation, making it present in the context of each historical and cultural circumstance. As will be presented below, this achievement could be completed only within the Church. Thus, Orthodox theology must deliver the eternal word and life of Jesus Christ, addressed to the contemporary context, in order to guide the Church and the Faithful toward the Kingdom of God. It is hoped that this comparative endeavour may be beneficial for general understanding between Christians, through placing in conversation two different perspectives regarding theology, which seldom encounter one another.